Distributed Autonomous Robotic Systems 8 2009
DOI: 10.1007/978-3-642-00644-9_23
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic Relationships for Optimizing Task Fulfillment in Robot Communities

Abstract: This paper introduces the concept of a multi-robot community in which mul tiple robots must fulfill their individual tasks while operating in a shared environment. Unlike typical multi-robot systems in which global cost func tions are minimized while accomplishing a set of global tasks, the robots in this work have individual tasks to accomplish and individual cost functions to optimize (e.g. path length or number of objects to gather). A strategy is presented in which a robot may choose to aid in the comple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The controller protects against selfish robots and is guaranteed to increase the level of altruism over time when the other robot reciprocates. See [6] for the stability analysis and extensive treatment of this controller.…”
Section: One-to-one Altruistic Controllermentioning
confidence: 99%
See 2 more Smart Citations
“…The controller protects against selfish robots and is guaranteed to increase the level of altruism over time when the other robot reciprocates. See [6] for the stability analysis and extensive treatment of this controller.…”
Section: One-to-one Altruistic Controllermentioning
confidence: 99%
“…In [6], it was demonstrated that the one-to-one controller successfully improves the individual cost functions of robots in a MRC (see Fig. 2).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Distributed auctions [Andersson and Sandholm 2000;Botelho and Alami 1999;Choi et al 2008;Clark et al 2008;Dias and Stentz 2002;Dias et al 2006b;Gerkey and Mataric 2002;Golfarelli et al 1997;Koenig et al 2007;McLurkin and Yamins 2005;Sandholm 1998;Zheng and Koenig 2009;Zlot and Stentz 2006] involve peer-to-peer redistribution of plans between given subsets of robots, where one of the robots serves as the auctioneer. This class of methods is the primary mechanism for providing intentional coordination between robots.…”
Section: Introductionmentioning
confidence: 98%
“…That is, these techniques can easily be ported to AUVs. One paper ( [12]) discusses robot altruism to optimize task fulfillment. Another, specific to AUVs, discusses cooperative multi-AUV control as it was used in the Autonomous Ocean Sampling Network discussed in Section 3.1.2 [15].…”
Section: Multiple Robotsmentioning
confidence: 99%